ANALISIS PENGGUNAAN SELEBRITAS VERSUS NON-SELEBRITAS PENDUKUNG PADA SIKAP TERHADAP IKLAN KOSMETIKA PRIA JENIS BEAUTY CARE DAN PROBLEM SOLVING - , Diah Prasita ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Suitability of the use of appropriate endorser at an advertisement product is important. The purpose of this study was to determine differences in perception on the endorser of celebrity and non-celebrity of male cosmetics advertisement. Aspects investigated differences include, attractiveness, honesty or trustworthiness, expertise or experience and attitude toward advertisement. The scope of the analysis also distinguished by the type of cosmetics , beauty care and problem solving. This study use a laboratory experiment conducted by 2x2 factorial design. This experiment was manipulated the variables of endorser that consists of celebrity and non-celebrity, as well as two types of cosmetics which consists of cosmetics beauty care and problem solving. Participants in this study amounted to 160 men who live in Palangkaraya and aged 20-35 years. Hypothesis testing using One-Way ANOVA as analysis tools. The study findings suggest that celebrity endorser is more effective than non-celebrity on male beauty care cosmetics. The celebrity excellence in physical attractiveness and expertise, while for trustworthiness aspect the non-celebrity was better than celebrities. The results of research on problem solving cosmetics shows that participants perceived celebrity more atrractive, but non-celebrity is more honest or trustworthiness than celebrity. In the aspect of skill or experience shows there is no difference between the use of celebrity and non - celebrity. Participant perceived celebrity more positive than non-celebrities on attitudes toward advertising on the type of cosmetic beauty care and problem solving. So the use of celebrity as endorser of cosmetics is better than a non-celebrity.